Manifestations of aggression in elite athletes - Petrovska, T.; Potop, V.; Sova, V.; Perepelytsia, A.; Bulhakova, T.; Folvarochnyi, I.; Korobeynikova, L.; Tolkunova, I.; Konyayeva, L. (Journal of Physical Education and Sport, 2021)
Purpose: to investigate the manifestations of the characteristics of aggressive and hostile behavior in athletes of different kinds of sports and sports qualifications. Material: The Bass-Darkey's technique was used to study the characteristics of aggressive and hostile behavior of athletes. The study involved 149 athletes of different sports and qualifications. Results: Our resuls was showed that high level of negativity and resentment in elite athletes link with competition activities. This fact indicates on increasing of aggressive behaviour in combat sport. The analysis of link between leve of aggresion and qualification in athletes are showed non elite athletes have a tendency to a overes parameters of physical, indirect and verbal aggression for concerning to elite athletes. The highest rates of aggressive and hostile behavior, significantly different from other sports, were found in the group of wrestlers and boxers. These results may be related to the specificity of the sports, psychological training and social support by the trainer. The high level of aggressiveness and hostility among low-skill athletes indicate is significantly different in terms of physical and indirect aggression, irritability and offense. Conclusions: The specificity of the sport and the orientation of its competitive activity influence the level and peculiarities of aggression and personal conflict of the athlete. Sports, in which aggressive actions are one of the main tools for achieving this goal, suggest the development of high levels of aggression and conflict in athletes. Aggression and hostility are not necessary qualities for high sport achievement, which is confirmed by their higher performance in athletes with low sports qualifications.